Transplantation: Beyond Transcultural and Identity-Making Processes (KULT_online, 2020)
The connection between the practical, physical realization of the botany-born concept of transplantation and its usage as cultural metaphor in identity-building aspects opens a range of questions regarding the problematic transferral of the concept from the scientific subject to the cultural disciplines. The interdisciplinary reconstruction of this conceptual fracture is investigated by the publication Kulturwissenschaftliche Konzepte der Transplantation (2019) edited by Ottmar Ette and Uwe Wirth, in collaboration with Carolin Haupt.